Extrusion of Snacks, Breakfast Cereals, and Confectioneries - Seker, Mahmut (Crc Press-Taylor & Francis Group, 2012)
[No abstract available]
Keywords: Twin-Screw Extrusion; Residence Time Distributions; Single-Screw; Physical-Properties; Carbon-Dioxide; Structural-Properties; Process Variables; Dietary Fiber; Cross-Linking; Co-Extrusion